Explaining individual differences in young English language learners' vocabulary knowledge: The role of Extramural English Exposure and motivation. (February 2021) - Leona, Nihayra L.; van Koert, Margreet J.H.; van der Molen, Maurits W.; Rispens, Judith E.; Tijms, Jurgen; Snellings, Patrick
Abstract: The role of motivation and extramural English exposure in explaining individual differences in young English language learners' (YELLs') English performance is unclear. In this study, we hypothesized that different types of extramural English exposure predict YELLs' (Dutch, N  = 262, 10 years old, grade 4) oral and written English receptive vocabulary knowledge, and that motivational factors act as mediators. A distinction was made between YELLs learning English only informally through extramural English exposure and YELLs learning English also formally at school. A path analysis showed that the total impact of familial extramural English exposure and extramural English exposure through entertaining media was greater for the YELLs learning English informally, compared to YELLs learning English also formally. While the sources of extramural English exposure were directly predictive of performance with regard to both oral and written English receptive vocabulary tests for YELLs' learning English informally, linguistic self-confidence fully mediated these relationships for YELLs learning English formally. Our findings call for further development of theoretical frameworks explaining the relationship between YELLs' motivation and exposure. Highlights: Extramural English exposure in the family and through entertaining media are important for English vocabulary knowledge. Linguistic self-confidence mediates the relationship between extramural English and vocabulary for formal English learning. Extramural English' effect is greater for YELLs learning English informally than for YELLs learning English also informally.